2019
DOI: 10.3390/ijms20184410
|View full text |Cite
|
Sign up to set email alerts
|

Production of IFNβ by Conventional Dendritic Cells after Stimulation with Viral Compounds and IFNβ-Independent IFNAR1-Signaling Pathways are Associated with Aggravation of Polymicrobial Sepsis

Abstract: Viral infections are associated with increased incidence of severe sepsis. Particularly during the early stages, type I interferons (IFNs) are known mediators of detrimental effects. However, the functional role of early interferon β (IFNβ) and its cellular source during sepsis in the context of preexisting viral infections has not been defined. Using the colon ascendens stent peritonitis (CASP) model, we demonstrate that IFNβ−/− and type I IFN receptor (IFNAR1)−/− mice were less susceptible to sepsis after pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Early studies first identified T1IFN signaling as deleterious in models of LPS‐induced peritonitis and septic shock, with mice deficient in IFNβ or T1IFN signaling components showing protection against LPS lethality 127,136,137 . Other studies similarly reported that T1IFNs contribute to hyperinflammation in peritonitis; in the colon ascendens stent peritonitis (CASP) model, IFNβ produced by cDC in response to prestimulation with the dsRNA mimetic poly(I:C) was associated with exacerbated disease in the early stages, 138 whereas IFNAR1 –/– mice were protected from severe disease, showing greater levels of neutrophil infiltration and bacterial clearance in the early stages, and reduced inflammation at later stages. 139 In a model of chronic peritonitis, IFNAR1 –/− mice were also protected against the accumulation of inflammatory monocytes, as a result of reduced CCR2 expression.…”
Section: Type I Ifnsmentioning
confidence: 99%
“…Early studies first identified T1IFN signaling as deleterious in models of LPS‐induced peritonitis and septic shock, with mice deficient in IFNβ or T1IFN signaling components showing protection against LPS lethality 127,136,137 . Other studies similarly reported that T1IFNs contribute to hyperinflammation in peritonitis; in the colon ascendens stent peritonitis (CASP) model, IFNβ produced by cDC in response to prestimulation with the dsRNA mimetic poly(I:C) was associated with exacerbated disease in the early stages, 138 whereas IFNAR1 –/– mice were protected from severe disease, showing greater levels of neutrophil infiltration and bacterial clearance in the early stages, and reduced inflammation at later stages. 139 In a model of chronic peritonitis, IFNAR1 –/− mice were also protected against the accumulation of inflammatory monocytes, as a result of reduced CCR2 expression.…”
Section: Type I Ifnsmentioning
confidence: 99%
“…Viral infections are associated with increased incidence of severe sepsis. The article by Dr. Howe identifies in the role of IFNβ and type I IFN receptor in mice susceptibility to sepsis using WT versus KO mice [ 9 ].…”
mentioning
confidence: 99%
“…The article by Dr. Gaffal reports the role of cannabinoid receptor 2 in modulating the maturation phenotype of DCs without affecting their chemotactic capacities using a murine model of contact hypersensitivity [8].Viral infections are associated with increased incidence of severe sepsis. The article by Dr. Howe identifies in the role of IFNβ and type I IFN receptor in mice susceptibility to sepsis using WT versus KO mice [9].Latent viral infection may also characterize multiple sclerosis patients as proposed in the communication by Dr. Corsetti in light of the enhanced activation of plasmacytoid dendritic cells from multiple sclerosis patients [10].Overall, this research topic highlights several aspects affecting DCs' maturation, activation, migration, and antigen presentation. Each one of these aspects is tightly regulated by a complex cascade of transcriptional factors and post-transcriptional regulators, which are known as microRNAs.…”
mentioning
confidence: 99%